2020
DOI: 10.1101/2020.06.14.150508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The bacterial effector HopZ1a acetylates MKK7 to suppress plant immunity

Abstract: 20The Pseudomonas syringae type III secretion system translocates effector proteins into 21 the host cell cytosol, suppressing plant basal immunity triggered upon recognition of 22 pathogen-associated molecular patterns (PAMPs), and effector-triggered immunity. 23Effector HopZ1a suppresses local and systemic immunity triggered by PAMPs and 24 effectors, through target acetylation. HopZ1a has been shown to target several plant 25 proteins, but none fully substantiates HopZ1a-associated immune suppression. Here,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Pathogens use effectors as key weapons to attack host plants because they can manipulate plant immunity by disrupting host protein function and promoting infection. For example, Pseudomonas syringae HopZ1a suppresses local and systemic plant immunity by acetylating mitogen-activated protein kinase kinase 7 (MKK7) (Rufian et al, 2021). The Magnaporthe oryzae effector AvrPiz-t suppresses the ubiquitin ligase activity of the rice RING E3 ubiquitin ligase APIP6 to suppress PAMP-triggered immunity (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogens use effectors as key weapons to attack host plants because they can manipulate plant immunity by disrupting host protein function and promoting infection. For example, Pseudomonas syringae HopZ1a suppresses local and systemic plant immunity by acetylating mitogen-activated protein kinase kinase 7 (MKK7) (Rufian et al, 2021). The Magnaporthe oryzae effector AvrPiz-t suppresses the ubiquitin ligase activity of the rice RING E3 ubiquitin ligase APIP6 to suppress PAMP-triggered immunity (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of plant immunity leads to a series of reactions, including an increase in reactive oxygen species (ROS), Ca 2+ influx, mitogen‐activated protein kinase activation, and regional cell death (Boller & Felix, 2009; Cheng et al, 2019; Spoel & Dong, 2012; Zipfel & Oldroyd, 2017). Numerous proteins, such as the transcription factor BZR1, which is involved in brassinosteroid signalling (Qi et al, 2021), mitogen‐activated protein kinase kinases (Rufian et al, 2021), and FLOWERING LOCUS KH domain (FLK) (Fabian et al, 2021), have been reported to regulate plant immune responses. Among these, FLK is an RNA‐binding protein (RBP) that regulates plant development (Lim et al, 2004), the ROS‐scavenging enzyme catalase, and plant immunity (Fabian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Type III effectors suppress PAMP‐triggered immunity (PTI) by targeting the biogenesis of PRRs, the activity and stability of PRRs, the co‐receptors of PRRs and the downstream signalling components of PRRs (Lee, Kim, Chae, & Oh, 2019; Macho & Zipfel, 2015). The suppression of PTI by effectors facilitates bacterial infection (Lee et al, 2019; Liu et al, 2017; Rufián et al, 2021; Sun et al, 2019). To defend against pathogens, some plants have evolved the second level of immunity, which is triggered upon the detection of specific type III effectors by intracellular nucleotide‐binding‐/leucine‐rich‐repeat receptors (NLRs) (Chisholm et al, 2006; Jones & Dangl, 2006; Laflamme et al, 2020).…”
Section: Effectors Play Key Roles In Bacteria–plant Binary Interactionsmentioning
confidence: 99%
“…In animal pathogens, YopJ homologues tend to interfere with the NF-κB pathway, the MAPK pathway, or both 111 . In plant pathogens, the function of YopJ homologues is far more diverse and less well-characterised; they can either play a role in inhibition of innate immunity or may exacerbate disease symptoms, depending on host species 112,113 . YopJ homologues have a conserved catalytic triad of histidine, aspartate/glutamate, and cysteine residues, which catalyse the transfer of an acetyl group from acetyl coenzyme A (acetyl-CoA) to the target protein [114,115].…”
Section: Yopjmentioning
confidence: 99%